EVALUASI PENGGUNAAN OBAT ANTIBIOTIK SEDIAAN INTRAVENA NON GENERIK PADA PASIEN RAWAT INAP DI RSUD 45 KUNINGAN - Asep Ilham; Herliningsih Herliningsih (Jurnal Farmaku (Farmasi Muhammadiyah Kuningan), 2018)
The use of a drug can affect the quality of treatment, service and medical expenses. As is. Based on the exposure, the researcher is interested to evaluate the use of drugs based on PERMENKES HK.02.02 / MENKES / 068 / I / 2010 to evaluate the use of non-generic intravenous antibiotic preparation drug in inpatient patients in RSUD 45 Kuningan. This research is an observational (non experimental) study of case studies using the population by observing a past, past or retrospective phenomenon, situation or problem. The results of the study that the authors obtained on the use of non-generic intravenous antibiotic preparations in January reached 11%, and in February it reached 9% with an average use of 10%. The Ministry of Health has issued a statement in 2010 that by 2014, 80-90% of prescriptions from doctors at public hospitals or puskesmas should be generic. From the regulation it can be concluded that the use of non-generic intravenous antibiotic preparation drugs in RSUD 45 Kuningan is appropriate and not deviated from the Regulation of the Minister of Health.